Retrieving translated Al-Quran documents using edit distance technique / Ahmad Syukri Mohamad Zaid - Mohamad Zaid, Ahmad Syukri (2001)
This paper describes features and methods for string searching and comparison using Wagner and Fischer algorithm. The method is used in developing search engine because of its speed and efficiency since it is based on dynamic programming. The approach has two main sections: the methodology used in implementing, and the result. The methodology used in implementing contains the checking step, and the calculation of Dice coefficient. The result is the produced result from experiment. The method has been implemented as a C programming language. The Wagner and Fischer is used to retrieve documents from the translated Al-Quran. Quantitative and qualitative comparisons are made between the different Dice coefficients. The comparisons show that smaller Dice coefficient gives quantitative results but larger Dice coefficient produces qualitative results.